2014
DOI: 10.1016/j.devcel.2014.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and Tissue-Specific Functions of Drosophila Doublesex Transcription Factor Target Genes

Abstract: Primary sex determination “switches” evolve rapidly, but Doublesex (DSX) related transcription factors (DMRTs) act downstream of these switches to control sexual development in most animal species. Drosophila dsx encodes female- and male-specific isoforms (DSXF and DSXM), but little is known about how dsx controls sexual development, whether DSXF and DSXM bind different targets, or how DSX proteins direct different outcomes in diverse tissues. We undertook genome-wide analyses to identify DSX targets using in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
168
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(184 citation statements)
references
References 79 publications
(99 reference statements)
9
168
1
Order By: Relevance
“…Of these, isoforms A, B, and C have detectable nervous system expression and are candidates for regulators of Lgr3 expression in the male nervous system (31). We examined the expression of R19B09.3A in flies individually mutant for the A, B, or C isoforms (13,28), and found that R19B09.3A expression was only affected by the absence of Fru B (Fig. 3 A and B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, isoforms A, B, and C have detectable nervous system expression and are candidates for regulators of Lgr3 expression in the male nervous system (31). We examined the expression of R19B09.3A in flies individually mutant for the A, B, or C isoforms (13,28), and found that R19B09.3A expression was only affected by the absence of Fru B (Fig. 3 A and B).…”
Section: Resultsmentioning
confidence: 99%
“…We attempted to address this question, as described below. Previous work identified regions of likely Dsx DNAbinding activity and a consensus 13-bp Dsx binding motif (GCAACAATGTTGC) (5,13,32). The Lgr3 locus contains three potential Dsx binding sites: a 9/13-bp partial binding site match in R17G11 (GagACAATGTgaC, with mismatches in lowercase), and two 10-and 11-bp partial matching sites in R17H01 (GCAACAtTGaaGt and GttACAtTGTTGC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In female somatic cells, Sxl controls the alternative splicing of transformer (tra), which together with transformer2 (tra2) controls the alternative splicing of doublesex (dsx) and fruitless (fru). dsx and fru in turn encode sex-specific transcription factors that control male versus female morphology, physiology, and behavior (3,4). In addition, Sxl represses the male-specific dosage compensation system by regulating male-specific lethal 2 (msl-2) both at the level of alternative splicing and translational control (5).…”
mentioning
confidence: 99%
“…[91][92][93][94][95][96] Both the isoforms of dsx act antagonistically on different targets present on multiple tissues with one being a positive regulator of certain gene in one tissue while negative regulator in others and vice versa. 97 Several other genes also play a role in the development of sex comb, for example, wg, dpp, Distal-less (DII), dachshund (dac), rotund (rn), and bric-a-brac (bab) ( Table 1). 97,98 Various types of pigmentation variations within and between closely related species are observed in many insect taxa as well as in Drosophila spp.…”
Section: Genetic Basis For Sexual Dimorphismmentioning
confidence: 99%